The Challenge of the Bad Man - Plaxton, Michael (McGill Law Journal / Revue de droit de McGill, 2012)
H.L.A. Hart’s insight, that some people may be guided by an offence provision because they take it as authoritative and not merely to avoid sanctions, has had an enormous influence upon criminal law theory. Hart, however, did not claim that any person in any actual legal order in fact thinks like the “puzzled man”, and there is lingering doubt as to the extent to which we should place him at the center of our analysis as we try to make sense of moral problems in the criminal law. Instead, we might find that our understanding of at least some issues in criminal law theory is advanced when we look through the eyes of Holmes’ “bad man”. This becomes clear when we consider the respective works by Hart and Douglas Husak on overcriminalization, James Chalmers and Fiona Leverick’s recent discussion of fair labeling, and Meir Dan-Cohen’s classic analysis of acoustic separation. These works also suggest, in different ways, that an emphasis on the bad man can expose the role of discretion in criminal justice systems, and the rule of law problems it generates.